БАГАТОКАНАЛЬНЕ КОНВЕРТУВАННЯ ВИПАДКОВИХ ДАНИХ ПАРНИМИ ЕЛЕМЕНТАМИ ВПОРЯДКОВАНИХ ВИБІРОК - Мазманян, Р.О. (Інститут електродинаміки НАН України, Київ, 2021)
The concept of multichannel parallel converting of probability density function (pdf) of random data was previously used for single-element pdf-converters. In development of this concept, here we investigate converting properties of spdf-converters channels formed by the sum of the ​​pairs of ordered sample elements (order statistics). The characteristics of the conversion results as dependencies on the size of the samples and the displacement of the channels relative to the median of the samples were obtained for data with a uniform distribution density.  Also where excluded the areas of mutual dependence of the density functions of the summed elements, which further where normalized together with  approximating them functions. Despite the apparent structural differences, the goal of this study still was to determine the closeness of the converted data with some standard functions of the probability distribution density, in particular, with the normal distribution law. As before, the estimates of the closeness of the spdf-converter channels were obtained using the chi-square criteria. The results of the research were used to determine the size and location of the statistical closeness windows, and to construct spdf-converters statistical model. References 20, figures 14.